A study of the indian taxation system on cryptocurrency - Arora, Jyoti; Kaur, Lakhwinder (Gyan Management Journal, 2023)
Cryptocurrencies are digital tokens that  allow people to make  payments directly to each other through an online system. Since it can  be used to buy and sell items and has the ability to store value and  increase in value, cryptocurrency is drawing the attention of a lot of  investors. As to the nature of cryptocurrency, there are different sets  of opinions as to whether it is a currency or a Commodity or Security.  The Finance Act 2022 was the first law to recognize Virtual Digital  Assets (VDAs) in India and introduced crypto taxes.  Accordingly,  the income generated from investment in cryptocurrency is subject to  tax. The present paper studies the emerging cryptocurrency market in  India and the provisions of prevailing income tax law in India related  to the taxation of cryptocurrency.
Keywords: Taxation; Cryptocurrency; Crypto assets; Virtual Digital Assets